Analysis of unsuccessfully performed throwing techniques by female competitors at Bosnia and Herzegovina state championship - Kajmovic, H.; Rado, I.; Kapo, S. (XX Scientific Conference in physical education, sport and recreation - (Nis, Serbia, october 19-21st, 2017) - Book of Proceedings, 2017)
The aim of this research is to analyze n=81 unsuccessfully performed throwing techniques by seniors on Bosnia and Herzegovina State Championship in judo, held in 2017. One third is related to successful throws while two thirds are unsuccessful throws. The largest number of unsuccessful throwing techniques is in leg (Ashi), hand (Te), side sacrifice (Yoko sutemi) and hip (Koshi) throws. The most unsuccessful throwing techniques are Ippon Seoi Nage, O Uchi Gari and Soto Makikomi. In the first place, the reasons for their failure are the lack of breaking the balance (Kuzushi) of their opponent, insufficient rotation during throws and attempt to attack from long distance. These results can be useful for trainers and contestants so they can, through the training process, work on reducing certain disadvantages during attempts of throwing their opponent.